The city as a cultural phenomenon (Journal of Philosophy Culture and Political Science, 2019)
In the scientiﬁ c article, urban culture is seen as a cultural phenomenon in the modernization of contemporary society. Reveals the virtual and ﬂ uctuating part of the modern city in the context of intercultural interaction. One of the main tasks of cultural analysis is a holistic approach to the problem of the modern city. The article describes that in the urban area concentrated energy centers and information resources. The meaning of life lies in a special «sign» of civilization and the author tries to reveal the codes of this complex phenomenon.